Analysis of students learning interest in biology subject matter of viruses in grade X senior high school - Muhammad Taufik Amin; Risma Delima Harahap (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
Virus concept biology subjects whose material is abstract in nature can generally reduce students' interest in learning. Students' interest in learning affects their learning outcomes both academically and non-academically. This study aims to analyze the learning interests of students at SMA Negeri 2 Bilah Hilir in the subject of virus concept biology. The samples in this study were students in class X MIA-1 and X MIA-2 with a total of 65 people. This type of research is qualitative research. The data collection technique uses a questionnaire of students' learning interest, and interviews as supporting data. The results showed that the indicators of students' feelings of pleasure in participating in learning were as large as and the involvement of students in learning received the "most" category, while the indicators of students' attention to the lesson and students' interest in learning received the "almost all" category. Based on the results of questionnaires and interviews it was concluded that the media, methods, and supporting facilities in schools in an integrated manner affect students' learning interest.Abstrak Mata pelajaran biologi konsep virus yang materinya bersifat abstrak umumnya dapat menurunkan minat belajar peserta didik. Minat belajar peserta didik mempengaruhi hasil belajarnya baik secara akademik maupun non akademik. Penelitian ini bertujuan untuk menganalisis minat belajar peserta didik di SMA Negeri 2 Bilah Hilir pada mata pelajaran biologi konsep virus. Sampel dalam penelitian ini adalah peserta didik kelas X MIA-1 dan X MIA-2 dengan total sebanyak 65 orang. Jenis penelitian ini adalah penelitian kualitatif. Teknik pengumpulan data menggunakan angket minat belajar peserta didik, dan wawancara sebagai data pendukung. Hasil penelitian menunjukkan indikator perasaan senang peserta didik dalam mengikuti pembelajaran sebesar dan keterlibatan peserta didik terhadap pembelajaran memperoleh kategori “sebagian besar”, sedangkan indikator perhatian peserta didik terhadap pelajaran dan ketertarikan peserta didik terhadap pembelajaran memperoleh kategori “hampir seluruhnya”. Berdasarkan hasil angket dan wawancara disimpulkan bahwa media, metode, dan sarana pendukung di sekolah secara terintegrasi mempengaruhi minat belajar peserta didik.